Factors Influencing Secondary Students' Choice of Business Studies as an Elective Subject - Budhathoki, Narayan Kumar (Journal of Business and Social Sciences, 2024)
This study examines the elements that influence the choice of Business Studies as an elective for Nepalese secondary students, focusing on intrinsic and extrinsic motivators and broader socio-economic and global influences. The study provides practical references to educators and policymakers to align their offerings with Nepalese students' needs and demands. A quantitative approach was used to collect data on students from both private and public schools. Data were analyzed by using descriptive statistics and t-tests to identify significant differences between private and public schools. The findings reveal that intrinsic factors such as career goals and personal interests significantly influence students selecting Business Studies. Similarly, extrinsic factors such as job prospects and supportive government policies positively influence students' choices. Students are less curious about the business world and have low perceptions of global opportunities for business studies. The study is limited only to the secondary students in Hetauda, Nepal. The study’s reliance based on self-reported data from respondents may introduce bias and hence limiting the generalization of the findings. Also, the result is limited to the analysis of present data. It does not provide past trends and longitudinal studies over time. The study offers practical references for educators and policymakers to make Business Studies more appealing through career counseling, and parents’ participation to align curriculum with economic opportunities. It also recommends the need for government subsidies and targeted support to promote business education. The study with the primary data from secondary students in Hetauda, Nepal, provides a unique and context-specific understanding of students’ decision-making processes. The findings are helpful for educators and policymakers pursuing enhancing the relevance and appeal of Business Studies in Nepal.